Grinding pyrolysis of Mallee wood: Effects of pyrolysis conditions on the yields of bio-oil and biochar - Hasan, MD Mahmudul; Wang, X.; Mourant, D.; Gunawan, Richard; Yu, C.; Hu, X.; Kadarwati, S.; Gholizadeh, M.; Wu, Hongwei; Li, B.; Zhang, Lei; Li, Chun-Zhu (Elsevier, 2017)
© 2017 Elsevier B.V. A novel technology termed as ‘grinding pyrolysis’ has been developed in response to the limitations hindering the commercialisation of existing fast pyrolysis technologies. Some of the features of this novel technology include capability of feeding biomass having a wide range of particle sizes in the same feedstock, simultaneous pyrolysis and grinding, no requirement for a fluidising gas and simplified requirement for cooling and condensing the pyrolysis products. A pilot plant was developed to study the effects of various operating conditions on the yields of bio-oil and biochar. Experiments have been done using mallee biomass grown in Western Australia. Feed particle sizes of up to a few centimetres have been used successfully. It was proved that the simultaneous grinding and pyrolysis helps liberating volatiles from a pyrolysing biomass particle and is capable of producing higher organic yields than pyrolysis without grinding. The effective size of a pyrolysing particle was significantly decreased by the si multaneous grinding activity.